First Evidence of Cryptic Species Diversity and Population Structuring of Selaroides leptolepis in the Tropical Western Pacific - Halasan, Lorenzo C.; Geraldino, Paul John L.; Lin, Hsiu-Chin (Frontiers in Marine Science, 2021)
The yellowstripe scad, Selaroides leptolepis (Carangidae), is an important fish commodity in the Tropical Western Pacific (TWP). It has a latitudinal Pacific range from south of Japan down to northern Australia, with the highest concentration in Southeast Asia. However, its TWP fishing grounds have long been a hotspot of unsustainable exploitations, thus threatening the remaining wild populations. Despite the species’ commercial significance, there is limited understanding of its genetic structure and diversity. Herein, the genetic structure of S. leptolepis was examined using mitochondrial COI and CytB sequences. Both markers denoted significant genetic structuring based on high overall FST values. Hierarchical analysis of molecular variance (AMOVA), maximum likelihood (ML) phylogenetic trees, and median-joining (MJ) haplotype networks strongly supported the occurrence of two allopatrically distributed lineages. These comprised of a widespread Asian lineage and an isolated Australian lineage. Within-lineage distances were low (K2P < 1%) whereas across-lineage distances were remarkably high (K2P > 6%), already comparable to that of interspecific carangid divergences. Haplotype sequence memberships, high genetic variations, and the geographic correlation suggested that the Australian lineage was a putative cryptic species. Historical demographic inferences also revealed that the species experienced rapid expansion commencing on the late Pleistocene, most likely during the end of the Last Glacial Maximum (∼20,000 years ago). The present study encouraged the application of lineage-specific management efforts, as the lineages are experiencing different evolutionary pressures. Overall, accurate knowledge of the species’ genetic distribution is fundamental in protecting its diversity and assuring stock sustainability.